Cytotoxicity of Kamandin Saebo Glossocardia leschenaultii [Cass.] Veldkamp Extract with Various Solvents on T47D Cells - Hasanah, Ulfatun; Budiyanto, Ratno; Triwahyuni, Novi; Badi’ah, Hanim Istatik (Indonesian Journal of Chemical Research, 2026)
In Indonesia, cancer is one of the diseases with a high mortality rate. In 2018, there were 348,809 cases of cancer, with 16.7% of all cases being breast cancer. In Indonesia, breast and cervical cancer are the most common types. The purpose of this study was to determine the secondary metabolite content of compounds and the anticancer activity of kamandin saebo extract against T47D breast cancer cells from kamandin saebo (Glossocardia leschenaultii [Cass.] Veldkamp) samples using various types of solvents. The methods used were sample preparation, moisture content analysis, extraction using the ultrasonic method, secondary metabolite analysis using reagents, and anticancer testing against T47D breast cancer cells. The plants were washed thoroughly to obtain powder and sieved with a 60 mesh, with a moisture content of 11.5% (w/w), and the extraction results obtained concentrated extracts from various types of solvents. The secondary metabolite content of kamandin saebo is flavonoids, steroids, alkaloids, and tannins. The anticancer activity of methanol, ethyl acetate, and n-hexane extracts, with IC50 values of 340, 272, and 107 µg/ml, respectively. The n-hexane extract has anticancer potential compared to ethyl acetate and methanol extracts.